The different characteristics of the recent eruptions of Fernandina and Sierra Negra volcanoes (Galápagos, Ecuador) - Vasconez, Francisco Javier; Ramón, Patricio; Hernandez, Stephen; Hidalgo, Silvana; Bernard, Benjamin; Ruiz, Mario; Alvarado, Alexandra; La Femina, Peter; Ruiz, Gorki (Volcanica, 2018)
After eight years of quiescence, Fernandina volcano experienced two short-lived eruptions, on 4-09-2017 and 16-06-2018. The eruptions were characterized by very short periods of unrest that started hours before the initiation of the eruptive activity. On the other hand, Sierra Negra volcano (Isabela Island) began a new eruptive period on 26-06-2018, after almost one year of persistent unrest characterized by an increase in the magnitude and number of seismic events and >5 m of uplift since its last eruption in 2005. The Sierra Negra and Fernandina eruptions were located in remote zones where access is extremely complex. Thus, satellite images complement the continuous monitoring data of the Instituto Geofísico with remote observations, allowing rapid response mapping to identify the areas affected by the lava flows. Finally, the aim of this Report is to encourage other scientists to investigate the behaviors of both pre-eruptive and eruptive periods registered during these eruptions.